PERGESERAN PARADIGMATIK TENTANG VALIDITAS HADITH NABI: Telaah Historis Istilah-Istilah dalam Kajian Kualitas Hadith - Mohammad Akib (IAIN Kediri, 2016)
The Quality of hadith which became a measure of the validity of the hadith is urgent. Among experts hadith, the Quality of hadith can be divided five variant, nemely sahih li dhatihi, sahih li ghairih, hasan lidhatihi, hasan lighairi and da’if. But the question is whether the emergence of terms simultaneously or based on a specific time dimension. The anwers for the questions are hat the terms conceptually not appear simultaneously and even tend to separate between one and the other. This reasoning is based on a fixed standard suggested by scholars of hadith especially al-Bukhari and Muslim. Both, very dominating compared to the compilers of kutub al – Sittah. Besides that, the frictions among scholars of hadith also give contributes to the distribution quality of hadith. They claim and make rules that lead to a different conclusion, although it remains aware that the accuracy of the theory remains dominated by certain scholars. Syahid and Tabi’ also contribute to the quality of hadith, though only a part of the external.Keywords; Quality of hadith, scholars of hadith, Syahid and Tabi’